2021
DOI: 10.3390/metabo11080507
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Alanine as a Potential Predictive Marker of Glioma—An Insight from Untargeted HRMAS-NMR and Machine Learning Data

Abstract: Metabolic alterations play a crucial role in glioma development and progression and can be detected even before the appearance of the fatal phenotype. We have compared the circulating metabolic fingerprints of glioma patients versus healthy controls, for the first time, in a quest to identify a panel of small, dysregulated metabolites with potential to serve as a predictive and/or diagnostic marker in the clinical settings. High-resolution magic angle spinning nuclear magnetic resonance spectroscopy (HRMAS-NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…These articles were screened by title and abstract, which returned 46 articles for a full-text review. Thirty-one articles were excluded, leaving 14 final studies included in this review, ten of which were included in the analysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Four studies were not included in the analysis because they did not perform an ML algorithm on GBM; however, they did discuss the topic [ 21 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These articles were screened by title and abstract, which returned 46 articles for a full-text review. Thirty-one articles were excluded, leaving 14 final studies included in this review, ten of which were included in the analysis [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Four studies were not included in the analysis because they did not perform an ML algorithm on GBM; however, they did discuss the topic [ 21 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Supervised ML is broadly used in a predictive scenario where a “ground truth” value can be determined (e.g., a diagnosis of GBM) and the user wishes to identify similar data sets with an unknown “ground truth.” The supervised ML algorithms used by these studies were SVM, random forest, ANN, deep neural networks (e.g., PASnet), DT, NB, partial least-squares discriminant analysis (PLS-DA), logistic regression models, and LASSO-penalized Cox regression analysis [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. A logistic regression model appears to outperform other ML algorithms in classification systems, in this case, the classification of the IDH mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a case-control study, alanine was reported to be a potential biomarker for malignant gliomas [45]. Similarly, glutamate was also found to play a central role in malignant gliomas through multiple mechanisms [46].…”
Section: Metabolite and Pathway Importance Analysismentioning
confidence: 99%